Overview Studi Kelayakan Bisnis Berkelanjutan di Indonesia - Abdi Hasibuan, Ilaika Fauziah; Joefanny, Dedek; Ilham Sembiring, M. Andreansyah; Vientiany, Dini (PENG: Jurnal Ekonomi dan Manajemen, 2025)
A business feasibility study is a crucial step in business planning and development, especially in developing countries like Indonesia, which face challenges of poverty and unemployment. This article examines the importance of a business feasibility study as a guide to understanding how to build a business and knowing the risks that may be faced. This research uses a library research approach or literature study method, conducting research on data collected from several books and journal publications. Feasibility studies focus on identifying market potential, where understanding consumer needs and preferences allows entrepreneurs to develop targeted products. In addition, evaluating financial aspects and identifying potential risks in feasibility studies helps entrepreneurs plan mitigation strategies that can protect investments and increase investor confidence. Operational aspects, such as location, management and supply chain, are also considered, because choosing a strategic location and efficient management has a direct influence on business success. Thus, this research concludes that a business feasibility study is not just a formality, but an important foundation for ensuring business sustainability. Through in-depth analysis, entrepreneurs can make better decisions and design effective strategies to face challenges, while getting support from other parties, such as banks and investors. A well-conducted feasibility study will give entrepreneurs the confidence to move forward and achieve success in a competitive business environment.